The Triplepidemic; Separating Truth from Fiction - Sajid, Zmareye; Arif, Shahmir (International Journal of Pathology, 2025)
Every fall and winter, a "tripledemic" convergence of respiratory viruses such as influenza, COVID-19, and RSV causes thousands of hospitalizations and deaths. The associated pathogens, which drive this seasonal crisis, comprise respiratory syncytial virus (RSV), human metapneumovirus (HMPV), coronavirus, enterovirus/rhinovirus, influenza virus (A and B being the cause of seasonal flu epidemics), parainfluenza virus, adenovirus, and human bocavirus (1). It is this simultaneous surge of RSV, COVID-19 and Influenza that defines the tripledemic’s unique danger and with rising rates being attributed to air pollution and emerging viruses; it is important to identify relevant public health measures to address the combined threat. Pakistan is currently ranked as the fifth most populous country with a population of 221 million, supplemented by a very high birth rate of 27 per 1,000. Viral illnesses affect 200 million children and elderly annually (1), displaying a typical "two-spike W-trend", however, healthy young adults can also be affected (2). Children under 5 years of age are more vulnerable to ARIs, reportedly responsible for a 16% incremental increase in the last decade, particularly in Pakistan, where respiratory infections account for 20% to 30% of all deaths (1). The tripledemic season significantly exacerbates this baseline burden.